Sinology in Kazakhstan: Past and Present - Muratbekova, A. (Journal of Oriental Studies, 2022)
China is a strategic neighbour of Kazakhstan. Studying China is also crucial for Kazakhstan's scholarship. Sinology, a subdiscipline of Oriental Studies that comprehensively works on China, is a relatively new field in Kazakhstan. Sharing a common border with China and having different forms of relations with China throughout history, Kazakhstan has only recently created its own school of Sinology. The reason was that, under the Soviet system, Kazakhstan had not had its own institution working on Oriental studies. The purpose of this paper is to examine the roots of Kazakhstan Sinology and analyse current developments in the school of Kazakhstan Sinology through a historical-analytical lens. The paper begins by introducing Sinology concepts and briefly describing Western and Chinese discussions on the concept of Sinology. Then, the historical evolution of Sinology in Soviet times unpacks the roots of Kazakhstan Sinology. The State of the Art of Sinology describes the latest developments in Kazakhstan, and in conclusion, the author proposes recommendations to advance Sinology studies in Kazakhstan. The paper contends that by combining Soviet and Western scientific traditions with local knowledge, Kazakhstan has a strong chance of establishing its own school of Sinology free of colonial legacy and Western-centric approach.